Avaliação do desempenho do procedimento recursivo do método dos elementos de contorno aplicados em problemas da elasticidade - Freitas, André Barbosa (2015)
In order to obtain more accurate results with lower computational cost, various pro-cedures and techniques have been evaluated and tested thoroughly. Among them, the recursive procedure is being studied for the boundary element method (BEM). The process consists of introducing a posteriori new source points on the contour, with distinct location of the original nodal points, in order to calculate values of the basic variable as is done to determine values at internal points. The procedure is based on the principles of Weighted Residual Method, so that re-application of the integral equation in the contour points is equivalent to a new resid-ual minimization. The technique was previously tested successfully in scalar field problems, and in this work is implemented with the elastic problems governed by the Navier equation. To use the recursive procedure, an analysis of the BEM hypersingular formulation was performed, noting their peculiarities and cautions. Several problems of elasticity were used so that the procedure could be compared with the direct method. We sought to evaluate the accuracy of the recursive procedure for the displacements and surface forces, showing that the procedure is effective in certain situations.